Performance and Techno-economic Analysis of a 1.82 kWp Rooftop PV System in the Tropical Climate of Indonesia: A Simulation vs Reality Approach - Rifaldi Wahyu Santoso; Dionova, Brainvendra Widi; Hamzah Eteruddin; Kalvin Saputra; Oo Abdul Rosyid; Fariz Maulana Rizanulhaq; Muhammad Irsyad Abdullah (Jurusan Teknik Elektro Universitas Andalas, 2026)
The utilization of renewable energy through rooftop photovoltaic (PV) systems serves as a strategic solution for mitigating climate change; however, their performance in tropical climates often exhibits a deviation between theoretical predictions and field reality. This study aims to evaluate the technical performance and economic viability of an on-grid 1.82 kWp rooftop PV system in Indonesia. The research employs a comparative quantitative approach by validating PVsyst simulation results against actual measurement data recorded from April to July 2024. The findings indicate a simulation overestimation, where actual energy production was 30.3% to 40.5% lower than PVsyst projections. A significant discrepancy was also observed in the Performance Ratio (PR), with the actual PR reaching only 55-59%, substantially lower than the simulated 81-82%. Despite these technical inconsistencies, the economic analysis confirms the project's financial feasibility. Under a 5.25% interest rate scenario, the study yielded a Net Present Value (NPV) of IDR 15.88 million, a Benefit-Cost Ratio (BCR) of 1.50, a Payback Period of 9.8 years, and a Levelized Cost of Electricity (LCOE) of IDR 974.88/kWh, more competitive than the national utility (PLN) tariffs. In conclusion, although tropical environmental factors such as high temperatures and dust accumulation reduce technical efficiency, rooftop PV investment in Indonesia maintains strong profitability and remains viable for implementation.